Analysis of essential oils through comprehensive two‐dimensional gas chromatography: General utility. (30th May 2017) - Tranchida, Peter Q.; Franchina, Flavio A.; Mondello, Luigi
Abstract: The first description of a comprehensive two‐dimensional gas chromatography (GC×GC) elucidation of an essential oil appeared in 2000 ( J. High Resol. Chromatogr. 2000;23:208‐214); since then, a variety of investigations have been published also involving complex samples related to essential oils, such as perfumes. In many instances, there was no mismatch between the use of GC×GC, and the analytical scope; on the other hand, in some specific cases the use of GC×GC appeared to be less adequate. The present contribution is focused on the application of GC×GC, within the context of essential oil analysis. Perfumes are also tightly related to essential oils, and so are herein considered. Rather than to describe and critically‐review all the research related to such investigations, attention has been devoted to the general analytical usefulness of GC×GC in the aforementioned application fields, over more established approaches, such as conventional GC and heart‐cutting multidimensional GC. Abstract : Filippi et al. carried out a detailed qualitative and quantitative analysis of four vetiver oils, namely Haiti, Indonesia, Brazil, La Réunion. 27 The GC‐QMS analysis of Haitian oil enabled the detection of 101 peaks, with a s/n exceeding 10. On the other hand, 535 peaks were detected by using GC×GC‐QMS, demonstrating the superior analytical power of the approach in this type of application. Moreover, the study of intra‐injector transformations was made much easier through use of the three‐dimensional method.